Kurangnya Tingkat Pengetahuan Pemberian ASI Eksklusif Di Desa Sipultak Dolok Kecamatan Pagaran, Siborong-Borong Tahun 2023 - Rizky Andriani Bakara; Emelia A. Tampubolon; Yermila Manao (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
This journal discusses community service activities carried out in Sipultak Dolok Village, Pagaran District, Siborong-Borong in 2023. The main focus of this service is education to increase mothers' level of knowledge regarding exclusive breastfeeding. The research was conducted in response to the lack of understanding of mothers in the village regarding the practice of exclusive breastfeeding. The methods used involve counseling, training and interactive activities to increase mothers' knowledge about the importance of exclusive breastfeeding. The results of the service showed a significant increase in mothers' understanding regarding the benefits of exclusive breastfeeding, correct feeding techniques, and its positive impact on the baby's health. This effort aims to empower mothers in Sipultak Dolok Village to provide optimal baby care through the practice of exclusive breastfeeding. It is hoped that improved understanding will have a positive impact on the health and development of children in the village.